Medical Students’ and Physicians’ Attitudes toward Patients’ Consent to Participate in Clinical Training - OMID, ATHAR (J Adv Med Educ Prof, 2015)
Introduction: The responsibility of the medical training team towards a patient referring to an academic medical center has not been fully clarified. In this article we have looked at current practice in Medical University of Isfahan and evaluated the attitude of the medical team towards patients’consent to be involved in medical students’education. Methods: In this cross-sectional study, conducted in 2012, we distributed self-administrated questionnaires among medical mentors, residents and students of academic hospitals in Isfahan, Iran. This researcher-made questionnaire consisted of several questions concerning dimensions of informed consent. The data were analyzed, using independent t-tests and ANOVA. Results: Ninety-one medical students (51 females) and 61 members of medical training team (25 females) completed the questionnaires. The overall average attitude score was 36.53±5.89 out of 60, which is classified as fair. The average attitude score for medical students and mentors were not significantly different. The average attitude score of the female students was classified as good, and was different from that of male students, significantly (p<0.05). By categorizing subjects into those with≥5 years of managerial or educational experience and those below 5, a significant difference in average attitude score was documented (35.8±2.54 in≥5and 34.0±2.9 in>5group). Conclusion: The attitude of the medical team is thoroughly far from what is expected. Thus, the need to provide both medical students and medical mentors with data on the importance of obtaining patients’ consent to be involved in medical education is highlighted.